Shipboard power system dynamic reconfiguration optimization strategy considering time-varying load characteristics - Qihuan WU; Zhiyu ZHU; Weihan HAO; Denghao YANG; Cheng XU (Zhongguo Jianchuan Yanjiu)
ObjectivesIn order to ensure the safe and stable operation of a shipboard power system under fault conditions, a dynamic reconfiguration optimization method is proposed that considers time-varying load characteristics.MethodsFirst, considering the topological structure, generation capacity limit, line current, node voltage and other constraints of the shipboard power system, a dynamic reconfiguration optimization strategy is proposed to minimize weight load cutting and voltage deviation. Next, an improved inertial particle swarm optimization algorithm is used to solve the optimization model. Finally, a typical shipboard power system is used as an example to verify the effectiveness of the proposed method.ResultsThe simulation results show that compared with the static reconfiguration method, the dynamic reconfiguration method can reduce the system's voltage deviation by 9.94%, thus significantly improving the quality of the network power supply.ConclusionsThe results of this study can provide references for the reliability design of shipboard power systems.